Análisis morfológico de grupos micorrízicos arbusculares presentes en sistemas agroforestales en la zona de Los Ríos - Cedeño Sánchez, Marcos Arturo (2022)
Soils are a fundamental component of the entire ecosystem, providing services such as food production, functions as a filter and gas exchanger, essential for the development of biota, among others. The concept of mycorrhiza is defined in a broad sense, as a symbiosis not necessarily mutualistic. Considering that arbuscular mycorrhizal fungi (AMF) colonize approximately 90% of vascular plants and that in agroforestry systems (AFS) there is a heterogeneous organization. Different investigations have shown that there is an interaction between different plants through colonizing AMF, these results indicate the effect of mycorrhizae on the development of cocoa plants. This interaction has potential for nutritional, sanitary and hydric control of SAF. In recent years, the interactions between plants and fungi, especially with arbuscular mycorrhizae, have aroused interest. Mycorrhizae represent symbiotic associations between plants and fungi based on the exchange of metabolites and nutrients. Studies in cocoa roots confirm the presence of structures of arbuscular mycorrhizal fungi such as arbuscules, vesicles and hyphae. This confirmed that there are high, medium and low values for the rate of infection in roots and population of spores in the soils of the studied areas. In the studied areas, the mycorrhizal genera were identified: Glomus spp., Acaulospora spp., Stecullopora spp., Rhizopogon spp. and Gigaspora spp. The prevalence of the Glomus genus with a high rate of number of spores in all sampled SAF-C soils, demonstrates the facility that representatives of this genus have to colonize cocoa roots. In addition, in our country very little is known about these beneficial microorganisms and obtaining these mycorrhizal fungi ensures the production of inocula that will serve as biofertilizer for plants.